Novel α-glycosyl compounds from glycosylation of rubusoside. (16th April 2023) - Wellmann, J.; Wilms, J.; Hartmann, B.; Zirpel, B.; Brückner, S.I.; Hillebrand, S.; Ley, J.; Winterhalter, P.
Highlights: Isolation and characterization of rare α-1, 3-glycosylated rubusoside derivatives. Structural characterization via ESI-IMS-QToF-MS and NMR. Sensory evaluation and comparison to previously known glycosylated rubusoside. Investigation of degradation by α-amylase from human saliva. Abstract: In this work we investigated mixtures from α-glycosylation of rubusoside with cyclodextrin glycosyltransferases. In addition to the previously known α-1, 4 glycosylated derivatives, nine new compounds with rare α-1, 3-glycosidic bonds were identified based on nuclear magnetic resonance spectroscopy and mass spectrometric analysis. Furthermore, sensory properties of monoglycosylated rubusoside derivatives were investigated and compared to previously described monoglycosylated compounds. Additionally, digestion with α-amylase from human saliva was investigated for different glycosylated rubusoside derivatives.